2023
DOI: 10.3390/su152115498
|View full text |Cite
|
Sign up to set email alerts
|

How Does Urbanization Affect Carbon Emission Performance? Evidence from 282 Cities in China

Zhibo Zhao,
Jiamin Ren,
Zheng Liu

Abstract: Improving carbon emission performance (CEP) is the key to realizing the goal of “carbon peaking and carbon neutrality” for China. Using a panel dataset of 282 cities at prefecture level and above in China from 2003 to 2017, this study employs the Global Malmquist–Luenberger (GML) index to measure CEP. Moreover, this study investigates the effect and transmission mechanisms of urbanization on CEP based on the extended STIRPAT model. The results show a significant positive “U-shaped” relationship between urbaniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 82 publications
0
0
1
Order By: Relevance
“…Wang et al [42] analyzed the relationship between urban size and per capita GHG emissions across 259 cities in China. They found that in small-and medium-sized cities (with populations under 1 million), the relationship between city size and per capita GHG emissions formed an inverse Ushape, while in larger cities (with populations over 1 million), it exhibited a U-shape [43]. Because they did not consider the compactness of the cities, caution should be exercised when directly comparing their findings with those of the present study.…”
Section: Discussioncontrasting
confidence: 53%
“…Wang et al [42] analyzed the relationship between urban size and per capita GHG emissions across 259 cities in China. They found that in small-and medium-sized cities (with populations under 1 million), the relationship between city size and per capita GHG emissions formed an inverse Ushape, while in larger cities (with populations over 1 million), it exhibited a U-shape [43]. Because they did not consider the compactness of the cities, caution should be exercised when directly comparing their findings with those of the present study.…”
Section: Discussioncontrasting
confidence: 53%